Influence of Prolonged Dental Bleaching on the Adhesive Bond Strength to Enamel Surfaces - Juliana C. P. Baia; Roberta P. Oliveira; Mara E. S. Ribeiro; Rafael R. Lima; Sandro C. Loretto; Mário H. Silva e Souza Junior (International Journal of Dentistry)
The objective of this in vitro study was to assess the influence of prolonged bleaching pre- and postrestoration on the bond strength (microshear) to enamel using 4% hydrogen peroxide (PH4). In the postrestorative bleached specimens evaluation, the composite cylinders were assembled after bleaching, while in the prebleached specimens, the cylinders were assembled before. Therefore, in the postbleached specimens, 60 bovine teeth were randomly assigned as follows: G1: control; G2: 14 days bleaching before bond strength (BS) testing; G3: 21 days; and G4: 28 days. In prebleached specimens, 180 bovine teeth were randomly assigned as follows: G1: control; G5: 14 days bleaching, storage in artificial saliva (AS) for 24 h before BS testing; G6: 14 days beaching, AS storage for 7 days before BS testing; G7: 21 days bleaching, AS storage for 24  h before BS testing; G8: 21 days bleaching, AS storage for 7 days before BS testing; G9: 28 days bleaching, AS storage for 24 hours before BS testing; and G10 : 28 days bleaching, AS storage for 7 days before BS testing. The results were submitted to ANOVA one-way (postrestoration bleaching) and two-way (prerestoration bleaching) and Tukey’s post hoc test (p≤0.05). In the postrestoration bleaching, no statistical difference between times was found. However, when bleached groups were compared to the control (G1), an expressive difference was detected (p≤0.0001). For prerestoration bleaching, all experimental groups were statistically different from G1 (p≤0.05), except G6 (p≥0.01), and for G5 and G6, statistical differences were found (p≤0.01). There were no significant differences between G7 and G8 and between G9 and G10, regardless of the AS storage times (p≥0.05). It was concluded that prolonged bleaching with PH4 decreased adhesion resistance regardless of the moment of the bleaching (post- and prerestoration bleaching).